The relevance of household contacts tracing among child contacts of patients with multidrug-resistant tuberculosis - O. M. Raznatovska; A. S. Moskaliuk; T. A. Grekova; L. I. Chernyshova; O. O. Pushnova; T. I. Shelestina (Infusion & Chemotherapy, 2020)
BACKGROUND. The World Health Organization (WHO) reports an unknown contact history of pediatric tuberculosis (TB), especially in children younger than 5 years old. Tracing pediatric household contacts of patients with multidrug-resistant TB (MDR-TB) is considered to be a highly effective intervention for detection of new cases of chemoresistant TB in children and timely prevention of its transmission.